FACTORS AFFECTING CORPORATE SOCIAL RESPONSIBILITY WITH ISLAMIC SOCIAL REPORTING METHODS - Ayu Sri Utari (IQTISHADUNA, 2020)
Measurement of Corporate Social Responsibility used in companies operating based on sharia at this time there are still many based on the Global Reporting Initiative Index (GRI) which is still conventional. Objective of this study is to analyze how the implementation of Corporate Social Responsibility by using IndexIslamic Social Reporting (ISR) in Islamic Banking in Indonesia and to examine how the influence of Company Size, and Leverage on the disclosure of Corporate Social Responsibility (CSR) in Islamic banking in Indonesia. The population of this study is all sharia commercial banks in Indonesia. The tested samples were totally 10 sharia commercial banks that selected by purposive sampling method. The method that used in this research is causality method with quantitative approach. This research analyzes CSR through annual report of sharia bank in 2014-2018 by using content analysis method. The technique of data analysis is panel data regression. The results of this study indicated that, from year to year All CSR indexes of sharia banks are fluctuating but tends to increase. Based on partial test, results of research indicate that Company Size has a positive and significant effect on CSR disclosure, while Leverage has no effect and is not significant on CSR disclosure. Based on simultaneous test, Company Size and Leverage have a significant effect on CSR disclosure.